2022
DOI: 10.3390/pharmaceutics14051042
|View full text |Cite
|
Sign up to set email alerts
|

3D Spheroids of Human Primary Urine-Derived Stem Cells in the Assessment of Drug-Induced Mitochondrial Toxicity

Abstract: Mitochondrial toxicity (Mito-Tox) risk has increased due to the administration of several classes of drugs, particularly some life-long antiretroviral drugs for HIV+ individuals. However, no suitable in vitro assays are available to test long-term Mito-Tox (≥4 weeks). The goal of this study is to develop a 3D spheroid system of human primary urine-derived stem cells (USC) for the prediction of drug-induced delayed Mito-Tox. The cytotoxicity and Mito-Tox were assessed in 3D USC spheroids 4 weeks after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 106 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…It provides a large number of cells and has gained attention for its potential in research, particularly human urinary exfoliated cells (USCs), which have shown promise as a source of cells for drug-induced nephrotoxicity testing in 3D models. This method offers the advantage of being non-invasive, making it more acceptable for routine research and potentially reducing costs compared to invasive procedures [6][7][8][9].…”
Section: Methods Of Obtaining Human Kidney Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…It provides a large number of cells and has gained attention for its potential in research, particularly human urinary exfoliated cells (USCs), which have shown promise as a source of cells for drug-induced nephrotoxicity testing in 3D models. This method offers the advantage of being non-invasive, making it more acceptable for routine research and potentially reducing costs compared to invasive procedures [6][7][8][9].…”
Section: Methods Of Obtaining Human Kidney Cellsmentioning
confidence: 99%
“…Precision nephrotoxicity testing aims to overcome these limitations by leveraging cutting-edge technologies such as genomics, proteomics, metabolomics and imaging to develop more accurate and sensitive biomarkers. In this review, we discuss precision nephrotoxicity testing using primary human renal cells in 3D in vitro models as a method for predicting druginduced kidney injury [6][7][8][9].…”
Section: Precision Nephrotoxicity Testingmentioning
confidence: 99%
See 3 more Smart Citations